Effect of proton beam irradiation on the tracking efficiency of CMOS image sensors. Issue 5 (3rd June 2022) - Fu, Jing; Feng, Jie; Li, Yu-Dong; Wen, Lin; Zhou, Dong; Guo, Qi
Abstract : A star tracker provides accurate space positioning and reference for satellites, intercontinental strategic missiles, and other spacecrafts. However, the main imaging unit of the star sensor – the image sensor – is affected by the space radiation environment and, in turn, affects the precision with which the star is located by the star tracker. In this study, the parameter degradation of a CMOS image sensor (CIS) after proton irradiation with different fluences was investigated. An outfield test platform for star map collection was built using the star sensor lens and image collection system. The influence of dark current, dark-current nonuniformity, and photo-response nonuniformity of the irradiated CIS on the star diagonal distance measurement error and star-point centroid position detection accuracy was studied. The results showed that with increasing proton fluences, the CIS noise increased, leading to an increase in the error in the measured diagonal distance of the star and a decrease in the star's position detection accuracy. Among these parameters, the dark current plays the greatest role in influencing the measurement accuracy of the star tracker. Furthermore, when a tracker is exposed to space radiation with fluences that are same as those used in this experiment, it is beneficial to reduce the integration time. This reduction in the time will decrease the noise and improve the position measurement accuracy.